Groundwater Vulnerability Study to Traditional Gold Mine Processing Pollution Using SYNTACS Method and GIS Approach - Farid Zulfa Fakhruddin; Mas Agus Mardiyanto (Syntax Corporation Indonesia, 2023)
Groundwater vulnerability study research conducted in Paya Ateuk Village, Pasie Raja District uses the SINTACS method. This method is an overlay method that combines 7 primary maps, namely soil texture maps, infiltration maps, slope maps, groundwater depth maps, rock unit maps, aquifer lithology maps, and hydroulic conductivity maps. Then the results of the assessment on the primary map parts are multiplied by the weight on the SINTACS classification and the results are combined into 1 groundwater vulnerability overlay map. The results of the map overlay produce 822 sections that have a range of groundwater vulnerability values ??at a score of 103.75 – 201.5 with low to high classification. Karst hill areas generally have moderate vulnerability values. Whereas in the lowlands with residential land use has a high vulnerability. This is due to the flat slope with sandstone, and moderate infiltration. Besides that, the texture of the soil is large and the depth of the groundwater is shallow. So that contamination on the surface can easily affect the quality of water in groundwater. Meanwhile, the groundwater vulnerability value is high in a narrow area with the use of paddy fields. Based on measurements of the quality of groundwater in wells owned by residents, it shows that the groundwater in the research location is of good quality. This is due to the large number of natural phytoremediation plants around the research area. Although the quality of groundwater is in good condition. The government as the policy maker still needs to regulate and provide official permits for traditional gold miners who are classified as illegal and continue to monitor the environment around traditional gold processing areas.